False positive 18FDG PET-CT results due to exogenous lipoid pneumonia secondary to oily drug inhalation: A case report. Issue 22 (June 2017) - Chardin, David; Nivaggioni, Guillaume; Viau, Philippe; Butori, Caherine; Padovani, Bernard; Grangeon-Chapon, Caroline; Razzouk-Cadet, Micheline
Abstract: Rationale: Exogenous lipoid pneumonia is a rare condition due to abnormal presence of oily substances in the lungs. It is a rarely known cause for false positive 18 FDG PET-CT results and can sometimes lead to invasive investigations. Searching and finding the source of the oily substance is one of the keys to the diagnosis. Inhalation of oily drugs during snorting has rarely been described. Patient concerns: A patient with well controlled HIV infection was referred for an 18 FDG PET-CT to assess extension of Kaposi's disease, recently removed from his right foot. The patient had no particular symptoms. Diagnoses: Abnormal uptake of 18 FDG was found in a suspicious lung nodule. An experienced radiologist thought the nodule was due to lipoid pneumonia. Interventions: Bronchoalveolar lavage fluid did not contain lipid-laden macrophages but bronchoscopy showed violet lesions resembling Kaposi's disease lesions. Lobectomy was performed after a multidisciplinary discussion. Outcomes: Anatomopathological analysis revealed the nodule was due to lipoid pneumonia. The patient's quality of life did not diminish after the operation and he is still in good health. The source of the oily substance causing lipoid pneumonia was found after the surgery: the patient used to snort oily drugs. Lessons: The presence of a suspicious lung nodule possibly due to lipoid pneumonia in a patient with known Kaposi's disease was difficult to untangle and lead to invasive surgery. It is possible that if a source of exogenous lipoid pneumonia had been found beforehand, surgery could have been prevented.